A CLINICAL APPROACH TO THE MIRROR NEURON SYSTEM AND ITS FUNCTIONS - Emre Harı; Canberk Cengiz; Ferhat Kılıç; Ertan Yurdakoş (İstanbul Tıp Fakültesi Dergisi)
Mirror neurons were discovered in macaque monkeys in the early 1990s by Rizzolatti and his colleagues at the University of Parma. In studies investigating mirror neurons in humans, noninvasive methods of neuroimaging and electrophysiology have been used because the invasive methods used on macaque monkeys are not available. Several complex functions, including identification, evaluation, and imitation of action, empathy, learning, and memory, have been attributed to this neuron group since its discovery. Thus, the mirror neuron system is thought to be the bridge between cognition and action. This possible role in cognition shows the contribution of this system in some neurological and psychiatric diseases. With this perspective, studies on the pathology of the mirror neuron system in Parkinson’s and Alzheimer’s diseases, amyotrophic lateral sclerosis, and autism-spectrum and psychotic disorders are mentioned in this review, together with research on the possible involvement of the mirror neuron system in congenital mirror movement disorder. A re-evaluation of neurological and psychiatric diseases in light of new opinions on the organization of the brain following the discovery of mirror neurons may be helpful in understanding clinical features and establishing new methods of treatment and rehabilitation.